Computerized Maintenance Management System (e-CMMS) / Nur Liyana Aziz - Aziz, Nur Liyana (2018)
Nowadays maintenance and repair management has a strategic role within organizations, it is responsible for ensuring the availability of equipment and facilities in the company or school. Sekolah Kebangsaan Sungai Petai is one of the organizations that is still implementing a partly computerized ways which use paper based and computer application which is not integrated. Computerized Maintenance Management System (e-CMMS) is a system that applies several elements of Computerized Maintenance system that consists five such as labor, asset management, work management, maintenance and notification of and followed evolutionary prototype model as method of system development. The system will record all the activity of the repairs and maintenances process including integrating the data. The evaluation for e- CMMS was conducted on 30 respondents and to three experts. In this research the expert give a comment to improve the system in two criteria which are perceived usability and satisfaction of system. The result shows that most of the expert agreed that e-CMMS is usable. Questionnaires was used as a tool to collect data that contain five construct which are System Capabilities Construct, Perceived Usefulness Construct, Satisfaction Construct, Ease of Use Construct, and Ease of Learning Construct. Results from the analysis specify that e-CMMS satisfied the respondent in term of usefullness with mean 4.533and for standard deviation is 0.571. The future enhancement for this e- CMMS is implementing a tracking function so that the user can identified data that close to due date.